2006
DOI: 10.1677/erc.1.01292
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-related receptor α as a therapeutic target in cancer

Abstract: The orphan receptor estrogen-related receptor a (ERRa) is a member of the nuclear receptor superfamily of ligand-regulated transcription factors. This protein is structurally most related to the canonical estrogen receptor and has been shown to modulate estrogen signaling in some contexts. These observations have heightened interest in ERRa as a therapeutic target in both breast and ovarian cancer and in other estrogenopathies. This review details our present understanding of ERRa action with a view to highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…There is mounting clinical evidence linking ERR␣ expression to tumor progression and less favorable prognoses in breast cancer patients (43,44,46,47). We have previously demonstrated that estrogens induce ERR␣ expression in MCF-7 cells, an ER␣-positive breast cancer cell line.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There is mounting clinical evidence linking ERR␣ expression to tumor progression and less favorable prognoses in breast cancer patients (43,44,46,47). We have previously demonstrated that estrogens induce ERR␣ expression in MCF-7 cells, an ER␣-positive breast cancer cell line.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, recent clinical studies implicate ERR␣ as having a potential role in breast cancer progression (43,44) based largely on its greater prevalence in ER␣-negative tumors and correlation with ErbB2, a known marker of aggressive tumors (45). Hence, positive ERR␣ expression is increasingly associated with an adverse clinical outcome and decreased chance of survival in breast cancer patients (46,47). ERR␣ may promote the growth of breast cancers by increasing local estrogen synthesis as it is reported to stimulate the expression of CYP19A1 (P450 aromatase) (48,49) and SULT2A1 (50), enzymes that contribute to estrogen biosynthesis.…”
mentioning
confidence: 99%
“…Recent evidence also suggests a role for epigenetic modulation in the process of adipocyte differentiation. microRNA (miR) 125-a inhibits the expression of estrogen-related receptor α (ESRRA) , an orphan nuclear receptor that modulates the activity of ESR1 in some tissues (Stein & McDonnell 2006). Inhibition of miR-125a leads to the promotion of porcine pre-adipocyte differentiation, whereas overexpression leads to alterations in lipid metabolism within adipocytes .…”
Section: Adipocyte Differentiationmentioning
confidence: 99%
“…An effective targeted therapy for these tumors is still not available (4). Lately, the orphan nuclear receptor ERRα emerged as a promising target for alternative treatment of breast carcinomas (5,6). Expression of ERRα in breast tumors correlates with an increased risk of recurrence, a poor prognosis of the patients (7), and high expression of the tyrosine kinase ErbB2 (Her2/neu; ref.…”
Section: Introductionmentioning
confidence: 99%